Pollen morphology and leaf epidermal micromorphology of 10 species of sect. Tuberculata(Camellia L.) - YAN Chao1, XIAO Xu1, RAN Zhaohui1, LI Zhi1,2* (Guangxi Zhiwu)
To provide research data for the phylogenetic evolution, classification and identification of plants in sect. Tuberculata of Camellia genus, 10 species of the section, leaf epidermal micromorphology and pollen morphology were observed by light microscope and scanning electron microscopy(SEM)and based on pollen features and leaf epidermal features to clustered separately. The results were as follows:(1)10 species had no significant difference in pollen morphology and size, the pollen shape was subspheroidal, prolate or oblatesphere; the outline in polar view was trilete rounded or trilete regular teiangular; the outline in equatorial view was oblong or fusiform, P/E ranged from 0.85 to 1.16; the aperature type was tricolporate aperature. The exine sculpture was significantly different, the feature had coarsely warty, foveolate reticulate or rugulate with beadedmun, and had important classification value for sect. Tuberculata.(2)The cluster analysis of the measurement index showed that when the Euclidean distance was 4.5, the 10 species were divided into four groups, and some of the classification results were the same as the macroscopic morphological classification.(3)The leaf epidermal cells of 10 species were irregular or polygon, with great morphological differences among species. There were glands in the upper and lower epidermis of C. zengii, C. rhytidophylla and C. rubimuricata; cyclic type stomatal apparatuses were only distributed in the lower epidermis; anticlinal wall pattern were sinuolate, sinuous, repand and sinuate.(4)The cell size and stomatal features(size and density)of leaf epidermis micromorphology were significantly different between species. This study shows that pollen morphology and leaf epidermal micromorphology are diverse in sect. Tuberculata, which can be used as the basis for distinguishing some closely related species in sect. Tuberculata.